SOCIAL SECURITY IN ITALY-TUNINSIA AGREEMENTS - BUCCHERI, CATERINA (e-Revista Internacional de la Protección Social, 2019)
Social Security fulfils the general principles of protection of the needy through social assistance and social security, specific for the safeguard of workers. In Italy, according to the principle of territoriality of the insurance obligation, the non community worker is subject to the country’s social security and welfare legislation. On 7 December 1984 an administrative agreement is signed in Tunis for the application of the convention on social security, between the Italian Republic and the Tunisian Republic, with the possibility for the Tunisian citizen to work in Italy, while remaining under the responsibility of the legislation on social security in your country of origin. Because of the political alternation of the Italian Governments, more restrictive guidelines have been reached, with the introduction of the limitation to equating to Italians only non-EU immigrants holding EC residence permits as long-staying guests, exceeding even the provisions of bilateral agreements including the Italy - Tunisian one. This has subordinated the provision of certain social security benefits, discriminating against Tunisian citizens and limiting the enjoyment of the fundamental rights recognized to Italian citizens.